A bioinformatics approach for identification of miR-100 targets implicated in breast cancer - Shamsi, R.; Seifi-Alan, M.; Behmanesh, A.; Omrani, M. D.; Mirfakhraie, R.; Ghafouri-Fard, S. (Cellular and Molecular Biology, 2017)
MicroRNAs (miRNAs) are small endogenous non-coding RNAs with principal roles in regulation of protein expression via translation repression and mRNA degradation. Based on these roles they are implicated in tumourigenesis processes as well. Among them is miR-100 which can exert both tumor suppressor and oncogenic functions in various cancer types. In breast cancer, it has been shown to affect apoptosis, epithelial-mesenchymal transition as well as tumor-related signaling pathways. In the present study, we introduce a novel approach for identification of miR-100 target genes which are possibly implicated in breast cancer pathogenesis. We applied 14 online tools for prediction of miR-100 target genes and used gene expression data produced by DNA microarray technology. By combining these two sets of data we proposed a list of miR-100 target genes with possible involvement in breast cancer. Considering the role of miR-100 as a context-dependent chief regulator of the cancer-related signaling pathways and a potential target for therapeutic modalities, identification of its targets would pave the way for designing new approaches for cancer treatment or sensitization of cancer cells to standard treatments.